A new method to reduce allergenicity by improving the functional properties of soybean 7S protein through covalent modification with polyphenols. (30th March 2022) - Lin, Xiao; Ye, Liying; He, Kan; Zhang, Tingting; Sun, Fan; Mei, Tiantian; Wu, Xuli
Highlights: A new method is proposed to reduce allergenicity of the soybean 7S Protein. Conjugation with polyphenols reduced the allergenicity of the 7S protein in vitro and vivo. Conjugation with polyphenols might mask or destroy epitopes on the 7S protein. Conjugation with polyphenols enhanced certain functional properties of the 7S protein. Abstract: The 7S fraction contains several major allergens of soybean protein. Here, the effects of covalent modification by chlorogenic acid (CHA) and (−)-epigallo-catechin 3-gallate (EGCG) on the allergenicity and functional properties of soybean 7S protein were investigated. Conjugation with EGCG and CHA resulted in the formation of cross-linked protein polymers and changes to the structures of the protein, which might mask or destroy the epitopes on it. In vitro analysis revealed that modification by polyphenols noticeably reduced IgE binding activity and histamine release. In vivo analysis showed that modification led to milder anaphylactic shock symptoms and minor damage of the intestine in mice, with reducing IgG, IgE, IgG1, mMCP-1, and histamine levels. The allergic response was also suppressed by the repression of IFN-γ, IL-4, and IL-5 and the up-regulation of IL-10 and TGF-β in the conjugate groups. Furthermore, modification enhanced antioxidant, emulsion, foaming capacity, and foam stability of the protein.